Inklusion - eine unerfüllbare Vision? Eine kritische Bestandsaufnahme - Graumann, Olga (Verlag Barbara Budrich, 2018)
Criticism of the implementation of school inclusion is growing and the question arises: where do we stand after 40 years of integration and inclusion experience? The vision of school inclusion is based on three pillars: the pillar of personal, structural and material framework conditions, the pillar of professionalism and the pillar of individual requirements as well as the tailor-made choice of school for the benefit of the child. The basis for the pillars is inclusion on a societal level. All three pillars currently have too many shortcomings to support the "inclusion" umbrella. Among other things, parents of children with disabilities who attended an integration class around 25 years ago were interviewed for the book. The school career of their children shows that integration into elementary school and comprehensive school is possible and successful if the necessary framework conditions are in place. However, interviews about the current experiences with school administrations, teachers and parents regarding inclusive schooling show how complex and contradictory inclusion is perceived by those affected and actors today and why inclusion is currently in danger of failing. Numerous practical examples of the implementation of inclusive didactics and inclusive structures in mainstream schools as well as the film accompanying the book about successful conditions for inclusive work in a primary school should encourage people to continue on the path to inclusion despite all the adversities.